The Wecken problem for coincidences of boundary preserving surface maps - Kelly, Michael R. (Topological Methods in Nonlinear Analysis, 2023)
We prove a Brooks type coincidence minimization result for boundary preserving maps on compact surfaces with boundary. As an application we obtain non-boundary Wecken results for pairs of maps $f,g\colon (X,\partial X) → (X,\partial X)$ for most surfaces $X$.